Role of Tropical Atlantic SST Variability as a Modulator of El Nino Teleconnections - Ham, YG; Sung, MK; An, SI; Schubert, S; Kug, JS (Asia-Pacific Journal of Atmospheric Sciences, 2014)
The present study suggests that the off-equatorial North Atlantic (NATL) SST warming plays a significant role in modulating El Nio teleconnection and its impact on the North Atlantic and European regions. The El Nio events accompanied by NATL SST warming exhibit south-north dipole pattern over the Western Europe to Atlantic, while the ENSO teleconnection pattern without NATL warming exhibits a Rossby wave-like pattern confined over the North Pacific and western Atlantic. Especially, the El Nio events with NATL warming show positive (negative) geopotential-height anomalies over the North Atlantic (Western Europe) which resemble the negative phase of the NAO. Consistently, it is shown using a simple statistical model that NATL SSTA in addition to the tropical Pacific SSTA leads to better prediction on regional climate variation over the North Atlantic and European regions. This role of NATL SST on ENSO teleconnection is also validated and discussed in a long term simulation of coupled global circulation model (CGCM). X 1 1 7 5 scie scopus kci